Dampak Kebijakan Merdeka Belajar Kampus Merdeka Untuk Tenaga Kependidikan - Kusworo Kusworo; Ubaid Al Faruq; Ibnu Sina (Faculty of training and education, Pamulang university, 2022)
The purpose of this study is to describe the perceptions of education staff related to the Free Campus Merdeka Learning (MBKM) policy in higher education environments. This type of research is quantitative research. The sample in this study is educational staff who work at Pamulang University with a total of 266 education staff. Data collection techniques using research questionnaires. The data analysis technique used is descriptive statistics. The results show that the knowledge of education staff related to MBKM such as policies that include the number of semesters and number of credit conversions, information on the MBKM program, study program activities related to the MBKM program, application of MBKM policies in tertiary institutions, involvement in MBKM activities, the impact of MBKM on hard skills and shift student skills, increase the capacity of educational staff. This shows that there is a good understanding and can be applied in accordance with the guidelines available in higher education. In addition, there is an increase in the capacity of education personnel related to the service of educational activities.Keywords: educational staff; MBKM; policy; University;